An improved location service scheme in urban environments with the combination of GPS and mobile stations. Issue 13 (1st May 2012) - Huang, Pengda; Pi, Yiming
ABSTRACT Satellite‐based apositioning and navigation technology in urban environments is widely studied. As a solution to GPS signal degradation in urban environment, the wireless network‐aided location scheme has been put into practice, which benefits our everyday life. However, there still exist many potential advantageous points that can be exploited to improve the performance of the location service especially in urban environments. This paper proposes a GPS‐based positioning and navigation with the aid of wireless network (GPONAWIN) positioning scheme that utilizes the existing resources of wireless communication networks to provide cheaper and more accurate urban positioning service with higher survivability. After the proposed scheme is described in detail, outperformances over the existing scheme are also analyzed. The GPONAWIN scheme can achieve higher information utilization efficiency, less wireless channel expenditure, more accurate positioning, better expandability to the multiple satellite positioning and navigation systems, and lower cost. Copyright © 2012 John Wiley & Sons, Ltd.